Renal Hemodynamics During Sympathetic Activation Following Aerobic and Anaerobic Exercise - Schlader, Zachary J.; Chapman, Christopher L.; Benati, Julia M.; Gideon, Elizabeth A.; Vargas, Nicole T.; Lema, Penelope C.; Johnson, Blair D. (Frontiers in Physiology, 2019)
We tested the hypotheses that prior aerobic (Study 1) or anaerobic (Study 2) exercise attenuates the increase in renal vascular resistance (RVR) during sympathetic stimulation. Ten healthy young adults (5 females) participated in both Study 1 (aerobic exercise) and Study 2 (anaerobic exercise). In Study 1, subjects completed three minutes of face cooling pre- and post- 30 min of moderate intensity aerobic exercise (68  1% estimate maximal heart rate). In Study 2, subjects completed two minutes of the cold pressor test pre- and post- the completion of a 30 s maximal effort cycling test (Wingate Anaerobic Test). Both face cooling and the cold pressor test stimulate the sympathetic nervous system and elevate RVR. The primary dependent variable in both Studies was renal blood velocity, which was measured at baseline and every minute during sympathetic stimulation. Renal blood velocity was measured via the coronal approach at the distal segment of the right renal artery with Doppler ultrasound. RVR was calculated from the quotient of mean arterial pressure and renal blood velocity. In Study 1, renal blood velocity and RVR did not differ between pre- and post- aerobic exercise (P≥0.24). Face cooling decreased renal blood velocity (P<0.01) and the magnitude of this decrease did not differ between pre- and post- aerobic exercise (P=0.52). RVR increased with face cooling (P<0.01) and the extent of these increases did not differ between pre- and post- aerobic exercise (P=0.74). In Study 2, renal blood velocity was 2 ± 2 cm/s lower post- anaerobic exercise (P=0.02), but RVR did not differ (P=0.08). The cold pressor test decreased renal blood velocity (P<0.01) and the magnitude of this decrease did not differ between pre- and post- anaerobic exercise (P=0.26). RVR increased with the cold pressor test (P<0.01) and the extent of these increases did not differ between pre- and post- anaerobic exercise (P=0.12). These data indicate that 30 min of moderate intensity aerobic exercise or 30 s of maximal effort anaerobic exercise does not affect the capacity to increase RVR during sympathetic stimulation following exercise.